Quand « l’exception » confirme la règle. L’encadrement juridique de la liberté de la presse écrite au Maroc - Ahmed Hidass (L’Année du Maghreb)
The pluralism of Moroccan media landscape is state organized and has two key purposes: firstly, legal and secondly, paralegal. The Constitution grants the freedom of expression nonetheless, unofficial red lines limit such right in practice. Mass media, the radio and TV, were for long monopolized by the state; however, since 2005, they have been opened to private stakeholders. Nevertheless, this organ of Makhzen establishment is still monochrome. It offers no academic interest and is widely challenged by satellite channels. Print media is an exception. It is owned by privates or political parties and faces, occasionally, state threats. It is regulated by the Constitutional provisions and the Press and Editing Code. It is a relevant indicator for the assessment of freedom of expression in Morocco. As per its circulation, it is a minor media. Issued under an authorization system, it is currently challenged by the websites media and its main titles are sponsored by the state. Few titles were independent. They have disappeared due to judicial harassment and advertizing boycott. But despite these difficulties, print media is an exception in Morocco and confirms an unwritten rule: freedom is granted under conditions.